Rage, Revenge, and Religion: Honest Signaling of Aggression and Nonaggression in Waorani Coalitional Violence - Boster, James S. (Ethos, 2003)
Until recently, the Waorani of eastern Ecuador engaged in a vicious cycle of revenge killing in which men responded to the death of kin by attacking their enemies. Yet their language, Wao tededo, lacks a label for the concept of 'revenge killing.'Apparently, a social pattern of revenge killing is not dependent on the recognition of 'revenge' as an abstract category— revenge need not be an overt cultural construction to be acted upon. This article explores this and other aspects of Wao ethnopsychology as they relate to the perpetuation and cessation of coalitional violence. It interprets Wao ethnopsychology in the light of Frank's (1988) account of emotions as honest signals of human commitment to social contracts. We argue that emotional displays of rage and the threat of retaliatory violence may deter an initial assault, but serve to lock antagonists into an endless cycle of violence once it has started. In order to end the cycle of violence, one needs a means to convey a message contrary to the enraged emotional one—an honest signal of one's commitment to end feuding. In the Waorani case, conversion to Christianity helped play this role.